The learning process for teaching academic writing, the case of Seventh Semester of the Career Pedagogía de los Idiomas Nacionales y Extranjeros at Universidad Nacional de Chimborazo in the city of Riobamba, Chimborazo Province during the academic period May 2021- September 2021 - Bermeo Barragán, Sara Elizabeth (2022)
Due to the updating of the regulations in the educational system, It was announced how the teaching-learning process of academic writing of the English language is taking place. The purpose of this research was to observe and identify how students are performing in the field of academic writing. A brief analysis was implemented with a certain group of students of the Pedagogía de los Idiomas Nacionales y Extranjeros career, which are in the Seventh Semester. It was achieved to know what the most effective way is to develop this skill, which was through self-learning among learners to discover both their strengths and weaknesses. In addition, they showed that writing essays in an academic way has a great influence on their training as a professional. On the other hand, it allows them to be critical and reflective by obtaining a clear communication in which they want to convey their writing. But at the same time, it is important to take into account what type of learning styles students frequently use to achieve quality learning, which are meaningful, collaborative and cooperative. Likewise, the teacher must pay attention with constant monitoring of the way in which their learners develop their activities, especially in what they still need to improve to have a broad command in this area of the English language. Some of the factors are being more critical, and not always taking good comments as good, but as feedback for an academic evolution.